THE DIMENSION OF COOPERATIVISM AND DAIRY CATTLE FARMING IN GETASAN VILLAGE, SEMARANG REGENCY, CENTRAL JAVA PROVINCE, INDONESIA - Gayatri, S.; Dizon, J.T.; Rebancos, C.M.; Querijero, N.J.V.B. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
The study was aimed to explore the role of cooperativism in dairy cattle farming in Getasan village,Semarang Regency, Central Java Province. Spearman Rank Correlation test was used to determine therelationship between cooperativism and the performance of dairy cattle farming. Based on the results ofthe Spearman Rank correlation test, feeds and feeding practices were significantly correlated withsharing of knowledge and information and sharing of resources. However, no significant relationshipwas found between participation in decision making and feeds and feeding practices. Meanwhile, therewere significant relationships amog sharing of knowledge and information, sharing of resources, andparticipation in decision making and milk production in Getasan Village. The dairy health asperformance indicator of dairy cattle farming, sharing of knowledge and information was the onlysignificant factor. Sharing of resources and participation in decision making had no significantrelationship with dairy health. As regards marketing, the test showed that sharing of knowledge andinformation, sharing of resources, and participation in decision making were significantly relatedfactors. This study indicated that cooperativism may provide opportunities for farmers to accessservices, information and resources that will allow them to improve their capacities in these areas. Thisstudy also proposed some recommendations that the cooperatives should promote activities encouraginggreater cooperation and mutual understanding among the members. Skills trainings and education forempowerment should be conducted to encourage participation in decision making.